Connectivity of Poissonian inhomogeneous random multigraphs - Lorenzo Federico (Electronic Journal of Graph Theory and Applications (EJGTA), 2023)
We introduce a model for inhomogeneous random graphs designed to have a lot of flexibility in the assignment of the degree sequence and the individual edge probabilities while remaining tractable. To achieve this we run a Poisson point process over the square [0, 1]2, with an intensity proportional to a kernel W(x, y) and identify every couple of vertices of the graph with a subset of the square, adding an edge between them if there is a point in such subset. This ensures unconditional independence among edges and makes many statements much easier to prove in this setting than in other similar models. Here we prove sharpness of the connectivity threshold under mild integrability conditions on W(x, y).